Pengaruh Tindakan Foot Massager terhadap Pencapaian Bromage Score pada Pasien Pasca Operasi Sectio Caesarea di Rumah Sakit Islam Purwokerto - M. Devin Kamal; Rahmaya Nova Handayani; Surtiningsih Surtiningsih (Jurnal Kesehatan Amanah, 2026)
The rate of Caesarean Section (CS) deliveries continues to increase, reaching 25.9% in Indonesia in 2023, with 24.9% in Central Java. Motor recovery after spinal anesthesia is evaluated using the Bromage Score, where a score ≤ 2 indicates the patient is ready to be transferredFoot massage, as a non-pharmacological intervention, is known to be effective in improving blood circulation, reducing muscle tension, and inducing relaxation, thus potentially accelerating recovery. This study aims to assess the effect of foot massage on achieving the Bromage Score in post-CS patients. This quantitative research method uses a quasi-experimental Posttest Only Control Group Design. Thirty respondents after CS surgery at Purwokerto Islamic Hospital were divided into two groups (15 intervention groups, 15 control groups) through total sampling. The results showed that the majority of the intervention group (80.0%) experienced an increase in the Bromage Score, in contrast to the control group (80.0% experienced no increase). The Mann Whitney test yielded a p-value of 0.000 (p < 0.05), indicating a significant effect of foot massage on achieving the Bromage Score. It was concluded that foot massage effectively accelerated motor recovery after CS surgery by increasing blood circulation, stimulating the parasympathetic nervous system, and accelerating neuromotor recovery.